Degradation of diesel oil by soil bacteria in shake flask system using food waste amendments - Gan, Sik Ze; Noraznawati Ismail,; Fazilah Ariffin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Diesel oil contains compounds that can cause harm to humans and the environment. Hence, biodegradation method is an alternative way to reduce the pollution caused by diesel oil. The aim of this study is to determine the diesel oil degradation by soil bacteria amended with food wastes in the flasks system. It also aims to determine the food wastes such as sugarcane bagasse and fishbone to enhance the biodegradation of diesel oil. The degradation analysis was performed in an enrichment culture flask containing soil, diesel oil with the addition of food waste. The degradation analysis was carried out for 42 days at 30°C at 150 rpm. The bacteria was isolated and identified based on colony morphology and biochemical tests. Five potential diesel oil-degrading bacteria were preliminary identified as Pseudomonas fluorescens, Pseudomonas aeruginosa, Klebsiella species, Shewanella putrefaciens and Bacillus cereus. Diesel oil degradation compound was analyzed using Gas Chromatography - Mass Spectrometry. Four compounds namely styrene, ethanol, 2-butoxy, benzene, 1-ethyl-2, 3-dimethyl and benzene 1-ethyl-2, 3-dimethyl showed degradation by bacteria amended with food wastes. The results of this study demonstrate the potential use of food wastes such as sugarcane bagasse and fish bone as substrates for enhancing the remediation of hydrocarbon contaminated soil.